2013
DOI: 10.1590/s1415-47572013005000034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and a selected core set of brazilian soybean cultivars

Abstract: Soybean is one of the most valuable and profitable oil crop species and a thorough knowledge of the genetic structure of this crop is necessary for developing the best breeding strategies. In this study, a representative collection of soybean cultivars recommended for farming in all Brazilian regions was genotyped using 27 simple sequence repeat (SSR) loci. A total of 130 alleles were detected, with an average allelic number of 4.81 per locus. These alleles determined the core set that best represented this so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 35 publications
1
20
0
5
Order By: Relevance
“…This indicates the influence of pedigree on STRUCTURE results. Similarly, a study of (Priolli et al 2013) showed that, after clustering soybean varieties assuming their pedigrees, varieties with similar ancestral origin were distributed into the same group. A large contribution of an ancestral variety, Lincoln, to the elite gene pool can be explained by its pedigree; it is developed from a cross between Mandarin and Manchu varieties.…”
Section: Discussionmentioning
confidence: 96%
“…This indicates the influence of pedigree on STRUCTURE results. Similarly, a study of (Priolli et al 2013) showed that, after clustering soybean varieties assuming their pedigrees, varieties with similar ancestral origin were distributed into the same group. A large contribution of an ancestral variety, Lincoln, to the elite gene pool can be explained by its pedigree; it is developed from a cross between Mandarin and Manchu varieties.…”
Section: Discussionmentioning
confidence: 96%
“…This panel can also be used in association studies to identify major genes or QTL controlling important traits. Core sets identified based on genetic markers are available in a number of field crops, like elite upland cotton (Tyagi et al, 2014), pima cotton (Xu et al, 2006), corn (Liu et al, 2003), soybean (Kuroda et al, 2009; Priolli et al, 2013), and fruit crops like watermelon ( Citrullus lanatus Thunb.) (Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, genetic diversity and LD were analysed with different molecular markers in ancestors of North American soybean cultivars (Zhu et al 2003) and in soybeans of Western Europe (Tavaud-Pirra et al 2009). Furthermore, similar analyses were performed in cultivated soybean landraces from China (Li et al 2008), in Korean and Chinese soybean accessions (Lee et al 2011), in Japanese landraces and varieties (Kaga et al 2012), in Brazilian soybean cultivars (Priolli et al 2013), in vegetable soybean from China (Dong et al 2014) and in multiple soybean populations including cultivars of different origin (Hyten et al 2007). Recently, sequencing (Schmutz et al 2010) and resequencing (Lam et al 2010, Li et al 2013) studies extended the work on genetic diversity and LD of soybean, but a detailed characterization of Central European soybean germplasm is lacking to date.…”
mentioning
confidence: 88%
“…), in Brazilian soybean cultivars (Priolli et al. ), in vegetable soybean from China (Dong et al. ) and in multiple soybean populations including cultivars of different origin (Hyten et al.…”
mentioning
confidence: 99%